Pengenalan Bantuan Hidup Dasar bagi Masyarakat di Desa Lane Kabupaten Pangkep - Abdul Rahman; Recky Recky; Fresly Aprilyana S; Fadliyah Fadliyah; Nurul Izathul C (Universitas Patria Artha, 2025)
An emergency is an urgent situation that poses a risk to health, life, well-being, or the environment. An incident can become an emergency if it threatens life, health, well-being, or the environment. This emergency situation requires the assistance of others who are ideally qualified to provide assistance. This requires the involvement of various parties, including first aid providers, technicians, and emergency health services. Emergency situations require immediate action. Sudden, unforeseen events are generally dangerous. Objective: To provide an understanding of Basic Life Support (BLS) to the community of Lane Village. Method: Lecture and Simulation Outcome: The community of Lane Village understands the concept of emergencies, first aid, and the steps in performing BLS.